App-based maintenance treatment for alcohol use disorder after acute inpatient treatment: Study protocol for a multicentre randomized controlled trial - Saur, Sebastian; Weisel, Kiona; Lang, Catharina; Fuhrmann, Lukas; Steins-Loeber, Sabine; Enewoldsen, Niklas; Reichl, Daniela; Zink, Mathias; Jakobi, Fabian; Rudolph, Melanie; Ahnert, Andreas; Braunwarth, Wolf Dietrich; et al. (Internet Interventions, 2022)
Background: Alcohol use disorder, a prevalent and disabling mental health problem, is often characterized by a chronic disease course. While effective inpatient and aftercare treatment options exist, the transferal of treatment success into everyday life is challenging and many patients remain without further assistance. App-based interventions with human guidance have great potential to support individuals after inpatient treatment, yet evidence on their efficacy remains scarce. Objectives: To develop an app-based intervention with human guidance and evaluate its usability, efficacy, and cost-effectiveness. Methods: Individuals with alcohol use disorder (DSM-5), aged 18 or higher, without history of schizophrenia, undergoing inpatient alcohol use disorder treatment (N = 356) were recruited in eight medical centres in Bavaria, Germany, between December 2019 and August 2021. Participants were randomized in a 1:1 ratio to either receive access to treatment as usual plus an app-based intervention with human guidance (intervention group) or access to treatment as usual plus app-based intervention after the active study phase (waitlist control/TAU group). Telephone-based assessments are conducted by diagnostic interviewers three and six weeks as well as three and six months after randomization. The primary outcome is the relapse risk during the six months after randomization assessed via the Timeline Follow-Back Interview. Secondary outcomes include intervention usage, uptake of aftercare treatments, AUD-related psychopathology, general psychopathology, and quality of life. Discussion: This study will provide further insights into the use of app-based interventions with human guidance as maintenance treatment in individuals with AUD. If shown to be efficacious, the intervention may improve AUD treatment by assisting individuals in maintaining inpatient treatment success after returning into their home setting. Due to the ubiquitous use of smartphones, the intervention has the potential to become part of routine AUD care in Germany and countries with similar healthcare systems.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Alcohol use disorder; App-based intervention; Germany; Human guidance; Maintenance treatment; RCT

Association of impulsivity with quality of life and well-being after alcohol withdrawal treatment - Reichl, Daniela; Enewoldsen, Niklas; Weisel, Kiona; Fuhrmann, Lukas; Lang, Catharina; Saur, Sebastian; Berking, Matthias; Zink, Mathias; Ahnert, Andreas; Falkai, Peter; Kraus, Thomas; Hillemacher, Thomas; et al. (Journal of Clinical Psychology, 2022)
Objectives Impulsivity is related to a higher risk of relapse in alcohol use disorders. However, besides drinking behavior, other recovery outcomes like physical and mental health-related quality of life are at least as important. The present study aimed to fill a research gap regarding the association of different impulsivity facets with health-related quality of life and well-being in alcohol use disorder. Methods Individuals with a primary alcohol use disorder diagnosis (n = 167) were interviewed with standardized self-report measures at the progressed stage of their withdrawal treatment and 6 weeks thereafter. Multiple regression models were calculated to examine the association of impulsivity, craving, and drinking patterns with health-related quality of life and well-being 6 weeks after withdrawal treatment, as well as the predictive role of impulsivity assessed during withdrawal for these two outcomes. Results Craving was associated with health-related quality of life and well-being 6 weeks after withdrawal. Likewise, non-planning and attentional impulsivity were associated with well-being 6 weeks after withdrawal. Motor impulsivity during withdrawal treatment predicted health-related quality of life 6 weeks thereafter. Conclusion Impulsivity seems to be negatively related to health-related quality of life and well-being in the first weeks after alcohol withdrawal treatment, probably to a higher extent than drinking patterns, but differentiating between its facets seems to be important. These findings emphasize the importance of treatment approaches aiming at reduced impulsivity in the early recovery process.
CRIS-Team WoS Importer:2022-02-04

Effects of Emotion Regulation Skills on Abstinence after Inpatient Treatment for Alcohol Use Disorder: A Latent Difference Score Analysis - Rupp, Lydia; Saur, Sebastian; Berking, Matthias (3. Deutscher Psychotherapiekongress (DPK), 2024)
Theoretischer Hintergrund: Alcohol use disorder (AUD) is a debilitating mental health problem, frequently developing into a chronic disorder (McKay & Hiller-Sturmhofel, 2011). While behavioral and cognitive treatments have been proven to be effective treatment approaches (Witkiewitz et al., 2019), barriers to adequate aftercare may increase risk for relapse and, thus, chronic development of the disorder (Buchholz et al., 2019). Therefore, understanding the mechanisms contributing to relapse risk may inform the development of effective aftercare and prevention strategies. A promising factor are emotion regulation skills, which have been shown to predict abstinence after psychotherapy for AUD (Berking et al., 2012). Fragestellung: Can emotion regulation skills predict abstinence in individuals with AUD after inpatient treatment? Methoden: We will use data of n = 356 individuals with AUD from a large randomized controlled trial on aftercare after inpatient treatment for AUD (Saur et al., 2022). AUD was diagnosed using the Structured Clinical Interview for DSM-5 Disorders-Clinician Version (First et al., 2016). Emotion regulation skills were assessed with the German version of the Emotion Regulation Skills Questionnaire (Berking & Znoj, 2008). Relapse and abstinence were assessed with the Timeline Follow-Back Alcohol interview (Sobell & Sobell, 1992). Outcomes were assessed before aftercare treatment (T1), mind-intervention (T2), six weeks after randomization (T3), and three (T4) and six months after randomization (T5). Data will be analysed using a Latent Difference Score approach (Hamagami & McArdle, 2001) to assess effects of emotion regulation skills on abstinence over time. Ergebnisse: Data analysis is underway and results will be presented. Diskussion: This analysis will build on and extend previous findings on the effects of emotion regulation skills on abstinence (Berking et al., 2012). We will replicate the results using a larger sample and a different analysis approach. The findings may help to develop more tailored and effective strategies for relapse prevention in AUD. This study addresses the limitations of the previous study (Berking et al., 2012) by including an untreated control group and using a standardized clinical interview for the diagnosis of AUD

Evaluation of a Smartphone App Intervention with Telephone Guidance as Transitional Support from Inpatient Treatment to Continuing Care for Individuals with Alcohol Use Disorder: Results from a Randomized Controlled Trial - Saur, Sebastian; Weisel, Kiona; Lang, Catharina; Fuhrmann, Lukas; Meurer, Niklas; Reichl, Daniela; Zink, Mathias; Heepe, Peter; Hillemacher, Thomas; Braunwarth, Wolf Dietrich; Falkai, Peter; Koller, Gabriele; et al. (Psychotherapy and Psychosomatics, 2025)
Introduction: Relapse rates in individuals with alcohol use disorder (AUD) are particularly high following inpatient treatment. Innovative strategies should specifically target the transitional gap between completion of inpatient treatment and uptake of standard continuing care. This study aimed to determine whether Appstinence, a digital approach that combines a smartphone app intervention with adjunct telephone coaching, more markedly reduces the risk of relapse for 6 months after inpatient AUD treatment in comparison to a control group with access to standard continuing care. Methods: In this multicenter clinical trial, 356 participants were randomized to the intervention (n = 175) or control group (n = 181). Eligibility criteria included diagnosis of AUD, smartphone access, no acute suicidality, and no language or neurocognitive impairments. The primary outcome was risk of relapse within 6 months after randomization, as assessed with the Timeline-Follow-Back method. Secondary outcomes included uptake of standard continuing care, hazardous alcohol consumption, craving, depression and anxiety symptom severity, and well-being. Results: The intervention reduced the risk of relapse within 6 months as indicated by a log-rank test (HR: 0.72, 95% CI: 0.53-0.98, p = 0.04) and Cox regression adjusted for baseline characteristics (HR: 0.67, 95% CI: 0.48-0.92, p = 0.01). This effect increased when participants fully adhered to the intervention protocol (log-rank test: HR: 0.61, 95% CI: 0.39-0.94, p = 0.02). No significant differences were observed in secondary outcomes. Conclusion: Our findings provide supportive evidence for digital AUD transition treatment. Specifically, we found that, in comparison with access standard continuing care, the novel intervention more effectively reduced risk of relapse within 6 months following inpatient treatment.
CRIS-Team Scopus Importer:2025-07-18
Keywords: Alcohol use disorder; Continuing care; Psychological treatment; Smartphone intervention; Telephone guidance

Lower Emotion Regulation Competencies Mediate the Association between Impulsivity and Craving during Alcohol Withdrawal Treatment - Reichl, Daniela; Enewoldsen, Niklas; Weisel, Kiona; Saur, Sebastian; Fuhrmann, Lukas; Lang, Catharina; Berking, Matthias; Zink, Mathias; Ahnert, Andreas; Falkai, Peter; Kraus, Thomas; Hillemacher, Thomas; et al. (Substance Use & Misuse, 2022)
There is evidence that craving mediates the relationship between Impulsive Personality Traits (IPTs) and relapse during the treatment of an Alcohol Use Disorder (AUD). To provide tailored interventions, a deeper understanding of the relation between IPTs and craving, namely mediating processes, is important. Based on previous literature, we proposed that lower emotion regulation competencies mediate the relation between attentional as well as non-planning IPTs and craving. To investigate these interrelations, we used data from the baseline assessment (n = 320) of the SmartAssistEntz project (pre-registered in the German Clinical Trials Register [DRKS00017700]). Inpatients with a primary AUD diagnosis were interviewed using standardized self-report measures (IPTs: BIS-15, emotion regulation competencies: ERSQ, craving: OCDS-G short version) during their withdrawal treatment. Indirect effects were calculated using the SPSS macro PROCESS v3.5. Attentional as well as non-planning, but not motor, IPTs were associated with craving. Emotion regulation competencies mediated the relationship between attentional as well as non-planning IPTs and craving. Given their mediating role in the present study, it is interesting to investigate if addressing emotion regulation competencies can mitigate the negative influences of attentional and non-planning IPTs. The direct effect of attentional IPTs implicates alternate mediating processes, which should also be investigated in future research.
CRIS-Team Scopus Importer:2022-03-04
Keywords: alcohol use disorder; attentional; AUD; impulse control; indirect; Motor; non-planning; withdrawal treatment

Nutzung von Anschlussmaßnahmen nach stationärem Alkoholentzug: Annahmen zum Stand der Vernetzung im deutschen Suchthilfesystem - Reichl, Daniela; Enewoldsen, Niklas; Tegethoff, Paulina; Gendlina, Taisia; Saur, Sebastian; Lang, Catharina; Fuhrmann, Lukas; Weisel, Kiona; Berking, Matthias; Zink, Mathias; Ahnert, Andreas; Falkai, Peter; et al. (Sucht, 2023)
Aims: The present study addresses potential problems with treatment transition by investigating the use of aftercare treatments by inpatients after alcohol withdrawal treatment without immediate transition to rehabilitation. Methods: We analyzed the control group of the SmartAssistEntz project. Therefor, 181 individuals were interviewed three and six weeks, as well as three and six months after their withdrawal treatment, assessing information regarding the use and evaluation of different aftercare treatments. Results: Over the course of the study, more than half of the participants reported using at least one aftercare treatment. Mostly and most continuously used were drug counseling offers (20-35 % of the participants). Rehabilitation treatments were reported by 8-14 % of the participants six weeks after withdrawal treatment, and by 27-33 % six months thereafter. The treatments were mostly considered to be "helpful", whereby self-help groups performed worst. The reason for the lack of aftercare was mostly waiting time (12-22 % of the cases). The use of rehabilitation treatment during the first three months after withdrawal treatment was associated with a reduced risk of relapse. Conclusions: Particularly drug counseling offers seem to be a low-threshold and subjectively helpful measure following inpatient withdrawal treatment. At the same time, regarding abstinence, the visit of rehabilitation treatments seems to be decisive. Thus, their use should be promoted more intensely.
CRIS-Team Scopus Importer:2023-12-01
Keywords: aftercare treatment; alcohol; health care; withdrawal treatment

Psychometric Evaluation of the German Version of the Substance Use Recovery Evaluator (SURE) - Reichl, Daniela; Enewoldsen, Niklas; Berking, Matthias; Fuhrmann, Lukas; Lang, Catharina; Saur, Sebastian; Weisel, Kiona; Steins-Loeber, Sabine (Diagnostica, 2022)
Consumption patterns and abstinence are popular, albeit insufficient, indicators in the recovery process from an alcohol use disorder (AUD). To meet the requirement of suitable measurement tools for a patient-centered recovery, we developed a German version of the Substance Use Recovery Evaluator (SURE), which we then evaluated in individuals with AUD at 6 weeks (2 subsamples: n = 135 and 120) and 6 months (n = 224) after withdrawal treatment. In the first subsample, we identified the factorial structure and calculated reliability and validity indices. In the second subsample, we checked the factorial structure by a confirmative analysis. The tool was shown to be reliable and valid. The original 5-factor structure showed a good fit, although a 3-factor structure was more suitable. These results were largely confirmed in the third sample. Despite some study limitations, the German version is a psychometrically valid measurement tool to assess the recovery from an AUD.
CRIS-Team WoS Importer:2022-10-07

Support after return to alcohol use: a mixed-methods study on how abstinence motivation and app use change after return to alcohol use in an app-based aftercare intervention for individuals with alcohol use disorder - Lang, Catharina; Weisel, Kiona; Saur, Sebastian; Fuhrmann, Lukas; Schönleber, Antonie; Reichl, Daniela; Enewoldsen, Niklas; Steins-Loeber, Sabine; Berking, Matthias (Addiction Science & Clinical Practice, 2024)
Background: As the return to alcohol use in individuals with alcohol use disorder (AUD) is common during treatment and recovery, it is important that abstinence motivation is maintained after such critical incidences. Our study aims to explore how individuals with AUD participating in an app-based intervention with telephone coaching after inpatient treatment perceived their abstinence motivation after the return to alcohol use, whether their app use behavior was affected and to identify helpful factors to maintain abstinence motivation. Methods: Using a mixed-methods approach, ten participants from the intervention group of the randomized controlled trial SmartAssistEntz who returned to alcohol use and recorded this in the app Appstinence, a smartphone application with telephone coaching designed for individuals with AUD, were interviewed about their experiences. The interviews were recorded, transcribed and coded using qualitative content analysis. App use behavior was additionally examined by using log data. Results: Of the ten interviewees, seven reported their abstinence motivation increased after the return to alcohol use. Reasons included the reminder of negative consequences of drinking, the desire to regain control of their situation as well as the perceived support provided by the app. App data showed that app use remained stable after the return to alcohol use with an average of 58.70 days of active app use (SD = 25.96, Mdn = 58.50, range = 24–96, IQR = 44.25) after the return to alcohol use which was also indicated by the participants’ reported use behavior. Conclusions: The findings of the study tentatively suggest that the app can provide support to individuals after the return to alcohol use to maintain and increase motivation after the incidence. Future research should (1) focus on specifically enhancing identification of high risk situations and reach during such critical incidences, (2) actively integrate the experience of the return to alcohol use into app-based interventions to better support individuals in achieving their personal AUD behavior change goals, and (3) investigate what type of support individuals might need who drop out of the study and intervention and discontinue app use altogether. Trial registration: The primary evaluation study is registered in the German Clinical Trials Register (DRKS, registration number DRKS00017700) and received approval of the ethical committee of the Friedrich-Alexander University Erlangen-Nuremberg (193_19 B).
CRIS-Team Scopus Importer:2024-05-10
Keywords: Abstinence motivation; Alcohol Use Disorder; App; Intervention; Mixed methods; Qualitative interviews; Relapse prevention; Telephone coaching

The effect of ethnicity and team membership on face processing: A cultural neuroscience perspective - Yan, Zhimin; Schmidt, Stephanie N. L.; Saur, Sebastian; Kirsch, Peter; Mier, Daniela (Social cognitive and affective neuroscience, 2019)
In-ethnicity bias, as one of the in-group biases, is widespread in different cultures, interfering with cross-ethnicity communication. Recent studies have revealed that an in-ethnicity bias can be reduced by an in-team bias caused by the membership in a mixed-ethnicity team. However, the neural correlates of different in-group biases are still not clear, especially regarding possible cultural differences. A total of 44 participants (20 Chinese and 24 Germans) were recruited and completed a social categorization fMRI-task, categorizing faces according to their ethnicity and a learned team membership. Our behavioral results revealed both in-ethnicity and in-team bias in German participants, but not in Chinese participants. Our imaging results, however, showed both biases across all participants, as reflected in increased dorsal medial frontal cortex (MFC) activation for in-ethnicity, as well as in-team categorizations, while activation in ventral MFC was higher for in-ethnicity faces in Chinese participants than in the German participants. Our results highlight the importance of the dorsal MFC for in-group categorization across cultures and suggest that cultures might modulate in-group biases.
Created from Fastlane, Scopus look-up
Keywords: cultural neuroscience; in-group bias; medial frontal cortex; social categorization